2014
DOI: 10.1016/j.evolhumbehav.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Who is the fairest of them all? The independent effect of attractive features and self-perceived attractiveness on cooperation among women

Abstract: Who is the fairest of them all? The independent effect of attractive features and self-perceived attractiveness on cooperation among women J. A. MUÑOZ-REYES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 78 publications
1
28
2
Order By: Relevance
“…Participants were asked to read and sign an informed consent form that detailed the procedure and the confidentiality steps. We used a standard coding process to preserve the anonymity of the participants 18,59 . All the participants signed the informed consent prior to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to read and sign an informed consent form that detailed the procedure and the confidentiality steps. We used a standard coding process to preserve the anonymity of the participants 18,59 . All the participants signed the informed consent prior to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, short-term effects of hormonal levels on asymmetry have been shown, as the asymmetry of facial shape changes during the menstrual cycle of individual women [294]. Finally, some human behavioral traits are also correlated with fluctuating asymmetry of facial shape, such as the tendency to cooperate or defect in the "prisoner's dilemma" game [374,375], some aggressive behaviors in adolescents [248], and personality traits [377,378].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%
“…In a study using a large combined sample from different Latin American countries, several factors were correlated to facial asymmetry: the strongest correlation was with age, but ethnic ancestry, heterozygosity, body mass index and height, as well as sex also had appreciable and significant effects [108]. Several studies have examined whether facial asymmetry is related to whether faces are rated as attractive by the subjects themselves or by other viewers, and some found a significant association [57,249,295,374], whereas others found no association [102,105] or a weak association only for male but not female faces [247]. Some analyses showed an association between fluctuating asymmetry and facial femininity or masculinity in humans [375], but others did not [102,374], nor was there a correlation between femininity or masculinity of skull shape and fluctuating asymmetry in baboons, chimpanzees, and gorillas [110].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the study by Mobius and Rosenblat (2006), in some experimental studies with economic games in which participants were asked to estimate the future cooperation of attractive players, the existence of a positive stereotype was confirmed (e.g., Mulford et al 1998;Wilson & Eckel 2006; but see Muñoz-Reyes et al [2014], in which participants had a right expectation about the uncooperative behavior of attractive players). No study, however, has provided evidence that the attractiveness stereotype is causally related to the preferential treatment of attractive people (see also Langlois et al [2000], who concluded that stereotype-based theories are largely unproven explanations of the attractiveness effects).…”
Section: Evidence In Favor or Against Different Explanationsmentioning
confidence: 53%